Analisis Proses Kenaikan Jenjang pada Jabatan Fungsional Pranata Humas di DPRD Kabupaten Sidoarjo - Khummad Robby, Tasbikhy; Noviyanti (Jurnal Inovasi Administrasi Negara Terapan, 2024)
Promotion to a functional position is an important aspect in developing an employee's career in a government organization. Apart from that, this promotion is a way to encourage work motivation and increase employee productivity. However, in the implementation of promotions to the functional positions of public relations officials at the Secretariat of the Sidoarjo Regency DPRD, there are obstacles experienced by the public relations officials concerned, namely in terms of time management, which causes delays in promotions to functional positions, which takes approximately 2 (two) year. The aim of this research is to describe the process of promotion in the functional positions of public relations institutions. This research uses a descriptive research method with a qualitative approach with data collection in the form of observation, interviews and documentation. There are research limitations, because the sources are outside the region. The results of this research describe that there are obstacles in making dupak, submitting the determination of credit figures and carrying out competency tests which have an impact on delays in promotion to the level of the public relations officer concerned. The advice given is that for the civil service section of the Sidoarjo Regency DPRD Secretariat, it is hoped that they will make a schedule for functional officials for those who will be promoted, and it is hoped that the Sidoarjo Regency BKD will include young expert public relations officers to take part in certification of technical expertise in assessing credit numbers, so that the assessment and determination of credit numbers can come from the district/city, and it is hoped that there will be mapping for promotions or promotions carried out by all OPDs both in the district/city/province as well as coordination between OPDs and BKN as organizers of competency tests which will facilitate implementation at the regional level.   Keywords: ASN Management, Functional Positions, Public Relations Institutions